Properties of molecular gas in galaxies in the early and mid stages of interaction. II. Molecular gas fraction. (20th June 2017) - Kaneko, Hiroyuki; Kuno, Nario; Iono, Daisuke; Tamura, Yoichi; Tosaki, Tomoka; Nakanishi, Kouichiro; Sawada, Tsuyoshi
Abstract: We have investigated properties of the interstellar medium in interacting galaxies in early and mid stages using mapping data of 12 CO( J  = 1–0) and H i . Assuming the standard CO–H2 conversion factor, we found no difference in molecular gas mass, atomic gas mass, and total gas mass (the sum of atomic and molecular gas mass) between interacting galaxies and isolated galaxies. However, interacting galaxies have a higher global molecular gas fraction $f_{\rm {mol}}^{\rm {global}}$ (the ratio of molecular gas mass to total gas mass averaged over a whole galaxy) at 0.71 ± 0.15 than isolated galaxies (0.52 ± 0.18). The distribution of the local molecular gas fraction f mol, the ratio of the surface density of molecular gas to that of the total gas, is different from the distribution in typical isolated galaxies. By a pixel-to-pixel comparison, isolated spiral galaxies show a gradual increase in f mol along the surface density of total gas until it is saturated at 1.0, while interacting galaxies show no clear relation. We performed pixel-to-pixel theoretical model fits by varying metallicity and external pressure. According to the model fitting, external pressure can explain the trend of f mol in the interacting galaxies. Assuming half of the standard CO–H2 conversion factor for interacting galaxies, the results of pixel-to-pixel theoretical model fitting get worse than adopting the standard conversion factor, although $f_{\rm {mol}}^{\rm {global}}$ of interacting galaxies (0.62 ± 0.17) becomes the same as in isolated galaxies. We conclude that external pressure occurs due to the shock prevailing over a whole galaxy or due to collisions between giant molecular clouds even in the early stage of the interaction. The external pressure accelerates an efficient transition from atomic gas to molecular gas. Regarding the chemical timescale, high f mol can be achieved at the very early stage of interaction even if the shock induced by the collision of galaxies ionizes interstellar gas.